Sports activities impact on ordinary mental reaction latency - Paužaitė, S. (Psichologija, 1962)
Practice needs are what raised the issue for reaction time research. This problem was first faced by astronomers. Physiologists investigated reaction time thereafter. The Donderso reaction time test method created in 1868 spread in mental processes research. Researchers studied the various factors that affect response time at the beginning of the 20th century. The importance of the ordinary mental reaction time research was not lost to Soviet and foreign psychology circles. Our task was to compare ordinary mental response time of athletes and non-of athletes, give an ordinary mental response characterization, and figure out factors that affect the reaction. The latency comparison showed that reaction is short for athletes, as well as their three-dimensional optical reaction. In their practical work they trained a rapid response to stimuli skills. Their sports activities had a positive impact on the reaction latency by shortening it. However, athletes did make more mistakes in responding. This emerged out of athletes' habit of responding in a motorized way and their greater tolerance for racing. From this we can conclude that the shortening of the latent period is not necessarily conclusive as an improvement in neurodynamic cortex condition. Thus, sporting exercises should be organized so that they would have a positive impact not only in terms of speed, but also for the correct response.
Keywords: reaction time; sports; ordinary mental reaction latency